איך אתה יכול להעריך (4a-2) / (3a + 12) - (א -2) / (א + 4)?

איך אתה יכול להעריך (4a-2) / (3a + 12) - (א -2) / (א + 4)?
Anonim

תשובה:

# (4a-2) / (3a + 12) - (a-2) / (a + 4) = 1/3 #

הסבר:

כדי לחשב את ההבדל בין שני המונחים, אתה צריך לכתוב אותם עם המכנה אותו. שים לב ש:

# 3a + 12 = 3 * (a + 4) #

לכן:

# (a + 2) / (a + 4) = a * 2 (a + 4) = (3 + a)) / (3 (a + 4)) = (3a-6) / (3a + 12) #

לכן:

מס '2 (4a-2) / (3a + 12) - (3a-6) / (3a + 12)

# = (4a-2) - (3a-6)) / (3a + 12) #

# (+ 4 + 3) + (3 + 12) = (4a-3a + 6-2) / (3a + 12) = (a + 4) / (3a + 12)

# = (a + 4) / (3 (a + 4)) = 1/3 #